Association between specific language impairment and behavioral disorders among preschool children - Kesuma, Yudianita; Rismarini, Rismarini; Theodorus, Theodorus; Azhar, Mutiara Budi (Paediatrica Indonesiana, 2014)
Background Specific language impairment (SU) is the most common developmental disorder in preschool children, causing serious impairmentE on behavioral development. To date, there have been few studies on SU and behavioral disorders in Palembang. Objective To assess for an association between SU and behavioral disorders in preschool children in Palembang. Methods Subjects in this cross-sectional study were children who attended kindergarten. Their general characteristics, developmental history and physical examination results (including weight and height) were recorded. We administered the Specific Language Impairment checklist for language impairment and the Pediatric Symptom Checklist 17 (PSC 17) for behavioral disorders. Data was analyzed by Chi-square test. Results We studied 1,340 children from21 kinderg:irtens in Palembang. Prevalence of SU was 12.9%, consisting of expressive language impairment (10.2%), receptive impairment (0.5%) and mixed language impairment (2 .2%). The prevalence of behavioral disorders was 15.1 %, consisting of internalization disorder (6.0%), externalization disorder (5.0%), attentive disorder (0.4%), and various combinations of three disorders (3. 7%). A highly significant association was found between SU and behavioral disorders (P=0.000; OR=2.082; 95% CI 1. 419-3 .053. Expressive language impairment was associated with externalization and mixed behavioral disorders. Mixed language impairment was associated with internalization, attentive, and mixed behavioral disorders. Howevei; receptive language disorder was not associated with any behavioral disorders. Conclusion SU is significantly as sociated with behavioral disorders. With regards to the individual SU types, expressive language impairment is associated with externalization and mixed behavioral disorders; mixed language impairment is associated with internalization, attentive and mixed behavioral disorders; but receptive language disorder is not associated with behavioral disorders.